Digital academic discourse: Texts and contexts: Introduction. (August 2018) - Kuteeva, Maria; Mauranen, Anna
Abstract: This Special Issue focuses on how digital media – blogs, tweets, and other digital platforms – are used by researchers, and how these new modes of academic communication have impacted writing practices and language uses in the academy. It brings together research in two related areas of scholarship: academic discourse analysis and literacies research. In this introductory article, we first outline the concept of digital academic discourse as we perceive it in the context of our Special Issue and show how it is related to, and at the same time different from, its "analogue" predecessor. We then continue to discuss the practices surrounding the production of academic texts with the support of digital media, followed by an outline of how both digital academic discourse and related writing practices are tied to the networks, communities and spaces in which they take place. Next, methodological issues in the study of digital academic discourse are considered, and the articles in this special issue are presented in connection to the themes outlined above. We conclude by contextualising the studies reported here within current trends in discourse analytical and sociolinguistic research and identify venues for future studies.